The karyotype of a rare south American marsupial, the bushy-tailed opossum genus Glironia (Didelphimorphia: Didelphidae) - Fantin, Cleiton; Silva, Maria Nazareth Ferreira da (Mastozoologia Neotropical, 2011)
We describe for the first time the karyotype of Glironia venusta (Didelphidae, Didelphimorphia), a rare South American marsupial. G. venusta has a diploid number 2n=18 and a number of autosomal arms NA=22. The diploid number of 18 chromosomes is somewhat unexpected, considering prior assignment of Glironia to the subfamily Caluromyinae (2n=14 in other species of the subfamily). The only other didelphid genus known to have 2n=18 chromosomes is Monodelphis. Chromosome banding, however, revealed a pattern closer to that observed for the 2n=14 species. Considering recent studies in didelphid phylogeny, wherein Glironia is sister to the remaining members of the family, the diploid number observed for Glironia may represent the ancestral state of the family, or may result from convergent evolution. © SAREM, 2011.
Cariotipo de un marsupial suramericano raro, zarigüeya de cola peluda, del género glironia (Didelphidae, didelphimorphia)